تربيـة المســاواة الجندرية بين الجنسين بالجـامعـة الإسلامية (State Islamic University (UIN) of Sunan Ampel Surabaya, 2010)
There are two definitions of gender equality. The first is according to United Nation Development Program and the second is in line with of Islamic view. The difference between its definitions lies in the implementation of total and balance equality. Total equality, as UNDP determiÂnes, is that woman and man are totally equal (50/50) in all aspects. But Islamic view suggests that both women and man are equal with harmony. The meaning of harmony does not just equality for woman and man in all aspects but also refer to difference between them. Sometimes woman have better chance than man, an in other times the fact suggests the reverse. But still other, woman and man have same good chance. To socialize this thinking and Islamic view, education hold an important role. Socialization can run in Islamic education institution. One of the Islamic education institutions is Islamic university.